LAND-BASED VECTOR MAGNETIC SURVEY OF A BIF-HOSTED IRON ORE DEPOSIT, MARY RIVER, BAFFIN ISLAND, NUNAVUT - Inozemtsev, Ilya (2015)
Banded iron formations (BIFs) are iron oxide- and silica-rich chemical sedimentary rocks and the principal source of high-grade (HG) iron ore. Magnetic survey methods are commonly applied in the exploration for BIF-hosted iron ore deposits but the interpretation of total magnetic intensity (TMI) data is often complicated by the presence of strong remanent magnetization and anisotropy of magnetic susceptibility (AMS). This study evaluated a tri-axial fluxgate vector magnetometer system for ground-based high-resolution mapping of BIF-hosted HG iron ore deposits at a 16 ha site near Mary River, Baffin Island. Magnetometer orientation was measured using a MEMS (Micro Electro-Mechanical System) accelerometer and dual D-GPS receivers. 12-oriented block samples were collected for analysis of rock magnetic properties and supplemented with outcrop measurements using a hand-held susceptibility probe. The large (3 Gauss) dynamic range of the tri-axial vector magnetometer permitted mapping of HG magnetite ore zones, with TMI in excess of 400,000 nT. A 20 m-wide W-E trending HG zone and a narrow (<10 m) BIF zone were identified in RMV maps with distinctive dipole signatures. Within the HG zone a northwest-southeast oriented magnetic fabric was defined by linear magnetic lows that offset the strike of the HG ore zone and were interpreted as brittle faults or shear zones. The RMV orientation indicated the presence of strong bedding parallel magnetization, while its signal amplitude showed a wide variation between ore types and provided basis for ore grade differentiation. Paleomagnetic measurements revealed high Q ratios for hematite ores and strong AMS for BIF. The results from Mary River demonstrate that remanence and AMS effects are important in BIF-hosted iron ores and cannot be neglected in magnetic interpretation and inversion modelling of magnetic source bodies. Thesis Master of Science (MSc)